Influence of internal blade-interactions on the added mass and added damping of a prototype Kaplan turbine runner - Ming Zhang (Elsevier, 2022)
Different from other types of hydraulic turbines, the fluid–structure coupling vibration behavior of Kaplan turbine runners has still been studied limited before. One problem is that their blades can rotate according to load changes, and the internal interactions among the blades via the flow field may produce an important influence on the added mass and added damping of the runner, particularly when the blade angle is small. In this paper, the influence of internal blade-interactions on the added mass and added damping of a prototype Kaplan turbine runner has been studied numerically. An isolated stage model from the end of the stay vanes to the bottom of the hub with six blades was considered for simulation. The Acoustic Fluid-Structure Interaction (FSI) technology based on the Finite Element Method was used to investigate the added mass effect first and to provide the modal shapes and initial frequencies for the following one-way FSI analysis based on the Finite Volume Method. The natural frequencies predicted by the Acoustic FSI were compared with those from the one-way FSI analysis to validate the simulations. Then, the influence of internal blade-interactions on the added mass and added damping, as well as the mechanisms, were analyzed.